2011
DOI: 10.1186/1741-7015-9-85
|View full text |Cite
|
Sign up to set email alerts
|

Strong association between non alcoholic fatty liver disease (NAFLD) and low 25(OH) vitamin D levels in an adult population with normal serum liver enzymes

Abstract: BackgroundHypovitaminosis D has been recently recognized as a worldwide epidemic. Since vitamin D exerts significant metabolic activities, comprising free fatty acids (FFA) flux regulation from the periphery to the liver, its deficiency may promote fat deposition into the hepatocytes. Aim of our study was to test the hypothesis of a direct association between hypovitaminosis D and the presence of NAFLD in subjects with various degree of insulin-resistance and related metabolic disorders.MethodsWe studied 262 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
241
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(264 citation statements)
references
References 39 publications
19
241
2
2
Order By: Relevance
“…Previous studies showed that low vitamin D levels were associated with the development of NAFLD, although the numbers of subjects included in the studies were small [17,18,22]. In contrast, a recent report by Katz et al that included 1,630 young adolescents did not find that vitamin D status was associated with suspected NAFLD (defined as elevated alanine transferase (ALT) levels only) after adjustment for obesity and metabolic syndrome [21].…”
Section: Anthropometric and Laboratory Measurementsmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous studies showed that low vitamin D levels were associated with the development of NAFLD, although the numbers of subjects included in the studies were small [17,18,22]. In contrast, a recent report by Katz et al that included 1,630 young adolescents did not find that vitamin D status was associated with suspected NAFLD (defined as elevated alanine transferase (ALT) levels only) after adjustment for obesity and metabolic syndrome [21].…”
Section: Anthropometric and Laboratory Measurementsmentioning
confidence: 69%
“…Because inflammation and oxidative stress might act as the common pathogenic mechanisms of NAFLD and vitamin D deficiency, and as both diseases are associated with insulin resistance, type 2 diabetes and cardiovascular disease, studies have been recently performed to examine the relationship of vitamin D levels with the development of NAFLD [17][18][19][20][21][22]. Previous studies showed that low vitamin D levels were associated with the development of NAFLD, although the numbers of subjects included in the studies were small [17,18,22].…”
Section: Anthropometric and Laboratory Measurementsmentioning
confidence: 99%
“…For example, low vitamin D favours intrahepatic lipid accumulation due to increased circulation of free fatty acids (FFA), which is regulated via the J Gastrointestin Liver Dis, June 2016 Vol. 25 No 2: 175-181 peroxisome proliferator-activated receptor gamma (PPAR-γ) [12,13]. Although not all [14,15], many observational studies report associations between vitamin D deficiency and hepatic steatosis [12,16], the aggregate effect of which has been illustrated in a meta-analysis [17] confirming the presence of decreased serum 25-hydroxyvitamin D concentrations in such patients.…”
Section: Introductionmentioning
confidence: 75%
“…The mechanisms by which vitamin D supplementation reduces hepatic steatosis are likely multifactorial. The fact that vitamin D can reduce FFA circulation, thus subsequently decreasing lipid acumulation via PPAR-γ provides an interesting concept [12]. Moreover, vitamin D regulates hepatic inflammatory and oxidative stress genes via VDR, which are causally implicated in hepatic steatosis [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, vitamin D deficiency has been proposed to be involved in autoimmune disorders, metabolic diseases, chronic viral infection, and tumors, including those affecting liver such as autoimmune hepatitis (Saron et al, 2009), alcoholic liver disease (Malham et al, 2011), nonalcoholic fat liver disease (Targher et al, 2007;Barchetta et al, 2011), chronic hepatitis C virus (HCV) infection (Arteh et al, 2010;Petta et al, 2010), and HCC (Chiang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%